Method Development and Validation of Sumatriptan In Bulk and Pharmaceutical Dosage Forms By UV Spectrophotometric Method. - Nayak, Rajesh Kumar (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT This paper describes the analytical method suitable for validation of Sumatriptan by UV Spectrophotometric method. The method utilized UV spectroscopy (Shimadzu, model 1700).The solvent system was consists of Methanol at wave length (Î» max) 282 nm. Validation experiments were performed to demonstrate System suitability, Specificity, Precision, Linearity, Accuracy Interday assay, intraday assay, robustness, ruggedness, LOD, &LOQ. The method was linear over the concentration range of 10-70 Âµg/ml. The method was showed good recoveries (99.28- 100.37%) and the recovery studies were carried out by adding different amounts (80%, 100% & 120%) of bulk samples of Sumatriptan. The Proposed method was simple, sensitive &reliable with good Precise, Accurate, and Reproducible and rapid for the determination of Sumatriptan. While estimating the commercial formulation without interference of excipients & other additives .hence this method can be used for routine determination of Sumatriptan in bulk and their pharmaceutical dosage forms.